Development of CTL-Based Handouts to Improve the Motivation and Learning Outcomes of Science Students in Grade VII - Ernia Nuraini; Ahmad Amin; Ovilia Putri Utami Gumay (CV. Dharma Samakta Edukhatulistiwa, 2025)
This researcher aims to develop handouts based on Contextual Teaching and Learning (CTL) to increase motivation and learning outcomes for Class VII students at SMP Negeri 7 Lubuklinggau. The method used is Research and Development (R&D) with a 4D development model but its application only reaches the 3D stage, namely: definition stage, design stage, development stage. The research sample or research subjects were students in class VII-2 of SMP Negeri 7 Lubuklinggau. The data collection technique uses a validation sheet. Based on validator analysis, it shows that the quality of learning media meets the very valid criteria with (1) 28 media validation results with a range of 25.2 < X ≤ 30, 21 language validation results with a range of 17.38, (2) increasing motivation 36.16 and 42.96 and (3) learning outcomes 0.58. So it can be said that the Contextual Teaching and Learning (CTL) based handouts were developed and validated as innovative teaching materials that can increase motivation and can be used in learning, with validation categories of good media expert, very good language expert, and very good material expert. Meanwhile, learning motivation shows a good category with an average N-gain of learning outcomes in the High category.